HPV E4 expression and DNA hypermethylation of CADM1, MAL, and miR124-2 genes in cervical cancer and precursor lesions. (December 2018) - Zummeren, Marjolein; Kremer, Wieke; Leeman, Annemiek; Bleeker, Maaike; Jenkins, David; Sandt, Miekel; Doorbar, John; Heideman, Daniëlle; Steenbergen, Renske; Snijders, Peter; Kenter, Gemma; Quint, Wim; et al.
Abstract In this study, we evaluate the expression of human papillomavirus E4 protein (marker for the onset of a productive infection) and hypermethylation of host-cellCADM1, MAL, andmiR124-2 genes (marker for an advanced, transforming infection) in cervical intraepithelial neoplasia (CIN) and cancer. A total of 115 cervical lesions were categorized by 3 pathologists into no dysplasia, CIN1, CIN2, CIN3, or cancer by classical histomorphological grading criteria, and by an immunoscore (cumulative value: 0–6) grading system based on Ki-67 (score: 0–3) and p16ink4a (score: 0–3) expression. Lesions were immunostained for E4 protein and analyzed for hypermethylation ofCADM1, MAL, ormiR124-2 genes. Expression of E4 and hypermethylation levels were related to CIN grade based on both classical and immunoscore grading. Hypermethylation increased with severity of the lesion as defined by both classical histomorphological grading and immunoscore criteria, and was always present in carcinomas (22/22). Extensive E4 expression decreased with increasing CIN grade and immunoscore, being most frequent in classically graded CIN1 or in lesions with cumulative immunoscore 1–3 and absent in carcinomas. High-grade lesions (CIN2/3 or immunoscore: 4–6) showed less E4 expression, which was inversely related to an increasing hypermethylation. Extensive E4 expression, as observed in a small proportion of high-grade lesions (6/49 and 8/43, respectively), was mostly associated with a negative methylation marker status (5/6 and 7/8, respectively). Our results illustrate the gradual transition of productive CIN (reflected by extensive E4 expression), to advanced transforming CIN (reflected by extensive hypermethylation) and cancer. Expression patterns of E4 and hypermethylation status of host-cell genes, may be used to identify cervical lesions at risk for cervical cancer, providing a better guidance for clinicians on treatment decisions.